DYNAMICS OF MILK PRODUCTION OF LATE LACTATION DAIRY GOAT FED PUFADIET SUPPLEMENTED WITH YEAST, C. xanthorrhiza Roxb, and THEIR COMBINATION - Asep Sudarman; Endang Sulistyowati; Komang G Wiryawan; Toto Toharmat; Sigit Mujiharjo (UNEJ e-Proceeding, 2017)
This article is a dynamics synthesis of milk production data of dairy goat fed diet containingconcentrate supplemented with PUFA (polyunsaturated fatty acid), yeast and curcuma. Twenty (20) dairy goats of Ettawa crossbred in late lactation phage were grouped into fiveof four goats to receive five treatments in in Randomized Complete Block design. Thetreatments were no supplement (PD0), 3 tablets of Asifit (PDA), 5g/d yeast (PDY), 20g/dcurcuma (PDC), and a mix of 5g/d yeast and 20g/d curcuma (PDM). The concentratecontained of PUFA sources (roasted ground corn, roasted soy bean meal, and corn oil),soybean by-product; roughage provided was King Grass. Milk yield was recorded daily, pre,treatment, and post then calculated all the way from pre to post treatment. Milk yield werehigher significantly (P<0.05) in PDA (538.7 g/d) and PDY (522.3g/d) compared to PD0(336.3g/d), PDC (322.3g/d) and PDM (392.0g/d). Average temperature and relativehumidity in the farm were 26.94 ± 2.280 C and 78.83 ± 7.34 %. Yeast supplementation eithersolely or in combination with curcuma is considered better in milk production dynamics inpre, treatment, post.